Penerapan Model Pembelajaran Problem Based Learning dalam Pembelajaran Matematika di Kelas VIII SMPN 28 Padang - Susanto, Andi; Ariadi, Sony (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This reseach is aimed at knowing the students ability in both solving the math problem and connection those who are taught by Problem Based Learning at class VIII of the Junior High school 28 Padang 2017/2018. This research is categorized as quasy Experimental Research, by using Randomized Control Group Only Design. After implementing the Problem Based Leaning, the student was directly given the test as the result showed that the scoreÂ of the student who belong to the experimental class inÂ problem solving recorded as 74,00 while those who were in the control class only refers to 72,30. The test average score on the experimental class in term of math connection ability was 68,73; while in the control class recorded as 62,43. The T- Test showed that T-Table equals to 1,64 with the degree of reliability 95% . This fact reveals that the studentsâ€™ ability in solving the problem after being taught through Problem Based Learning is higher than in control class with T-count equals to 3,71; while their connection math ability through Problem Based Learning Model in the Experimental Class is higher than control with T-count 2.17.Keywords: Problem Based Learning, problem solving, mathematics connection